1957
DOI: 10.1136/jnnp.20.3.202
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Transneuronal Atrophy in the Human Lateral Geniculate Body

Abstract: The phenomenon of atrophy in nerve cells after loss of their afferent connexions has been known for many years, but has been demonstrated unequivocally only in the lateral geniculate body, where it results from the degeneration and loss of afferents from the retina. It is shown by a diminution in the size of the perikaryon of the neurones, a somewhat variable loss of Nissl granules, a loss of intercellular neuropil (due to degeneration of fibres from the retina), and glial proliferation. Although often describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

1962
1962
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 3 publications
3
31
1
Order By: Relevance
“…Since traumatic neuropathy did not appear to be a major factor in the present study, it follows that the loss of functioning motor units must have resulted from trans-synaptic degeneration of motoneurones. This type of degeneration has been studied most fully in the lateral geniculate nucleus after section of the optic nerve (Glees and Le Gros Clark, 1941;Cook, Walker, and Barr, 1951 ;Goldby, 1957;Hess, 1957;Matthews, Cowan, and Powell, 1960). The occurrence of trans-synaptic degeneration in the mammalian spinal cord is less widely accepted, however, for although authors such as Barron (1933) and Young (1966) have reported motoneurone degeneration following spinal transection, others have attributed this to interference with the blood supply of the cord.…”
Section: Discussionmentioning
confidence: 99%
“…Since traumatic neuropathy did not appear to be a major factor in the present study, it follows that the loss of functioning motor units must have resulted from trans-synaptic degeneration of motoneurones. This type of degeneration has been studied most fully in the lateral geniculate nucleus after section of the optic nerve (Glees and Le Gros Clark, 1941;Cook, Walker, and Barr, 1951 ;Goldby, 1957;Hess, 1957;Matthews, Cowan, and Powell, 1960). The occurrence of trans-synaptic degeneration in the mammalian spinal cord is less widely accepted, however, for although authors such as Barron (1933) and Young (1966) have reported motoneurone degeneration following spinal transection, others have attributed this to interference with the blood supply of the cord.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of vacuoles and myelin figures within lateral gen iculate neurones is of particular interest in the context of neuronal atrophy and even loss of neurones reported by a num ber of in vestigators both in aging | Brody, 1960;Wright and Spink, 19591 and following lesions of the visual pathw ay [Goldby, 1957;Glees et al, 1967 ]. The role, if any, of lipofuscin in the ultim ate loss of post m itotic cells, however, continues to remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…This process, which is called trans-synaptic or transneuronal degeneration, is a critical component of the disease progression in many neurological disorders. [14][15][16][17][18] Transneuronal anterograde degeneration is the degeneration of a target neuron after the death of the presynaptic neuron or loss of the presynaptic input. [3][4][5][6] However, the TRD occurs when neurons degenerate after the removal of their postsynaptic target.…”
Section: Discussionmentioning
confidence: 99%